The Effect of Scramble Media on Improving The Ability to Compose Simple Sentences of Deaf Students - Putri, Novia Kelana; Priyono, Priyono; Supratiwi, Mahardika (Department of Special Education, 2024)
This study aims to determine the effect of Scramble media on improving the ability to compose simple sentences for deaf students in class IV B at Sekolah Khusus Tunarungu Surakarta. This study used an experimental approach in the form of pre-post experimental design one group pre test-post test design. The subjects in this study were all deaf students totaling 6 students. This study uses a sampling technique that is non-probability sampling. The technique used in data collection is a written test in the form of multiple choice objective tests. Data analysis technique used is non-parametric statistics with Wilcoxon Sign Rank Test. The results of descriptive analysis obtained the average value of the post test is greater than the pre-test value, namely 57.80 to 88.33. Furthermore, the results of the analysis of the Wilcoxon Sign Rank Test showed that the Zhitung value was -2.214 and the Asymp- Sig (2-tailed) was 0.027 with a significance level (α) of 0.05 or 5%. It can be concluded that Asymp-Sig (2-tailed) is smaller than the significance level or 0.027